Corporate reputation in management research: a review of the literature and assessment of the concept - Annika Veh; Markus Göbel; Rick Vogel (Business Research, 2019)
The study of reputation figures prominently in management research, yet the increasing number of publications makes it difficult to keep track of this growing body of literature. This paper provides a systematic review of the literature based on a large-scale bibliometric analysis. We draw on bibliographic data of 5885 publications published until 2016, inclusively, and combine co-citation analysis and bibliographic coupling with network visualization. Results show how research on corporate reputation is embedded in the broader field of scholarship on reputation in general. When zooming into the publication cluster on corporate reputation more closely, the concept's origins in economics, organizational studies, and marketing as well as corresponding theoretical and methodological discussions are revealed. Beyond providing a structured overview of the field, the bibliometric analyses also reveal conceptual incoherencies that lead to ambiguities in research. Our assessment builds on the philosophy of science and is guided by the criteria of good concepts in social sciences. It shows that the concept of corporate reputation lacks internal coherence and could have more theoretical utility. We recommend focusing on corporate reputation as an attitudinal concept and thereby emphasizing the stakeholder who acts as an evaluator of the corporation.
Keywords: 650; Bibliometrics; Bibliographic coupling; Co-citation analysis; Concept formation; Corporate reputation